2023
DOI: 10.1002/pul2.12200
|View full text |Cite
|
Sign up to set email alerts
|

Aggrecan accumulates at sites of increased pulmonary arterial pressure in idiopathic pulmonary arterial hypertension

Abstract: Expansion of extracellular matrix occurs in all stages of pulmonary angiopathy associated with pulmonary arterial hypertension (PAH). In systemic arteries, dysregulation and accumulation of the large chondroitin‐sulfate proteoglycan aggrecan is associated with swelling and disruption of vessel wall homeostasis. Whether aggrecan is present in pulmonary arteries, and its potential roles in PAH, has not been thoroughly investigated. Here, lung tissue from 11 patients with idiopathic PAH was imaged using synchrotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 54 publications
(140 reference statements)
0
1
0
Order By: Relevance
“…Signaling pathways include signaling by GPCR [56] and extracellular matrix organization [57] were responsible for advancement of HD. Research has shown that CBLN2 [58], MOG (myelin oligodendrocyte glycoprotein) [59], ROS1 [60], LGR6 [61], GJA5 [62], SUCNR1 [63], REN (renin) [64], VEGFC (vascular endothelial growth factor C) [65], TLR2 [66], FGF12 [67], WT1 [68], SLC22A3 [69], CSRP3 [70], PAPPA2 [71], ACAN (aggrecan) [72], SHH (sonic hedgehog signaling molecule) [73], PDC (phosducin) [74], AGTR1 [75], XDH (xanthine dehydrogenase) [76], P2RX7 [77], NTSR1 [78], SIRT2 [79], RBP4 [80], BMP2 [81], ERBB3 [82], HAS2 [83], CDH13 [84], CSMD1 [85], NR3C2 [86], EPAS1 [87], TRPC6 [88], MMP3 [89], ERAP2 [90], HLA-DRB1 [91], CD74 [92], VWF (von Willebrand factor) [93], MTTP (microsomal triglyceride transfer protein) [494], ANGPT2 [184], AKR1C3 [495], NEDD4L [496], CASP1 [497], LDB2 [498], CHRNA5 [499], CCND2 [500], BRCA2 [97], ZBTB20 [501], EFNB2 [502], CYP7B1 [503], DCLK1 [504], RBM20 [505], PLCE1 [197], protein) [94], NEDD4L [95], CASP1 [96], BRCA2 [97], EFNB2 [98], PLCE1 [99], EGFR (epidermal growth factor receptor) [100], ABCA1 [101], CRHR2 [102], RND3 [103], COMT (catechol-O-methyltransferase) [104] and SMAD9 [105] plays an important role in the pathogenesis of hypertension. Studies have revealed that NEUROD4 [106], SOX10 [107], MOG (myelin oligodendrocyte glycoprotein) [108], NR5A2 [109], GLRA3 [110], FA2H [111], SERPINA […”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathways include signaling by GPCR [56] and extracellular matrix organization [57] were responsible for advancement of HD. Research has shown that CBLN2 [58], MOG (myelin oligodendrocyte glycoprotein) [59], ROS1 [60], LGR6 [61], GJA5 [62], SUCNR1 [63], REN (renin) [64], VEGFC (vascular endothelial growth factor C) [65], TLR2 [66], FGF12 [67], WT1 [68], SLC22A3 [69], CSRP3 [70], PAPPA2 [71], ACAN (aggrecan) [72], SHH (sonic hedgehog signaling molecule) [73], PDC (phosducin) [74], AGTR1 [75], XDH (xanthine dehydrogenase) [76], P2RX7 [77], NTSR1 [78], SIRT2 [79], RBP4 [80], BMP2 [81], ERBB3 [82], HAS2 [83], CDH13 [84], CSMD1 [85], NR3C2 [86], EPAS1 [87], TRPC6 [88], MMP3 [89], ERAP2 [90], HLA-DRB1 [91], CD74 [92], VWF (von Willebrand factor) [93], MTTP (microsomal triglyceride transfer protein) [494], ANGPT2 [184], AKR1C3 [495], NEDD4L [496], CASP1 [497], LDB2 [498], CHRNA5 [499], CCND2 [500], BRCA2 [97], ZBTB20 [501], EFNB2 [502], CYP7B1 [503], DCLK1 [504], RBM20 [505], PLCE1 [197], protein) [94], NEDD4L [95], CASP1 [96], BRCA2 [97], EFNB2 [98], PLCE1 [99], EGFR (epidermal growth factor receptor) [100], ABCA1 [101], CRHR2 [102], RND3 [103], COMT (catechol-O-methyltransferase) [104] and SMAD9 [105] plays an important role in the pathogenesis of hypertension. Studies have revealed that NEUROD4 [106], SOX10 [107], MOG (myelin oligodendrocyte glycoprotein) [108], NR5A2 [109], GLRA3 [110], FA2H [111], SERPINA […”
Section: Discussionmentioning
confidence: 99%